Assessment on Strength Characteristics of Microbial Concrete by using Bacillus Subtilis as Self-healing Agent: A Critical Review - Priyom, Sudipto Nath; Ismal, Md. Moinul; Shumi, Wahhida (International Journal of Sustainable Construction Engineering and Technology, 2021)
Concrete is one of the most widely used construction materials by mankind and it is the main material used for the infrastructure development of every country. Microbial concrete, as the name suggest is an improvisation provided to cement using living microbes which are capable of doing so. Using microbes such as Bacillus subtilis which has the properties of bio-calcification can secrete calcium carbonate as an extra cellular product. Thus, filling the pores and the cracks internally, it makes the structure more compact and resistive to seepage. In this experimental investigation, the performance of microbial concrete exposed to plain water. Concrete specimens of 100 mm cubical size were cast and cured for 7, 14, 28, 60, 90 days in plain water with and without using bacterial water. Using a spectrophotometer to measure the optical density at 600 nm (OD600) of a bacterial culture to monitor bacterial growth has always been a central technique in microbiology. Concrete specimens having OD600 0.107, 0.20, 0.637 and 1.221 have been studied in plain water. The specimens were taken out periodically and subjected to compressive & tensile strength tests. From the investigation, it has been revealed that microbial concrete having OD600 0.637 shows better resistance against strength deterioration under all curing conditions and curing ages. Concrete specimens were also subjected to Ultrasonic Pulse Velocity (UPV) test. From this test, it has been observed that specimens having OD600 0.637 shows better velocity. The higher pulse velocity can therefore be used to assess the quality and uniformity of the material